Analysis of company performance measurement using the balanced scorecard method and analytical hierarchy process (AHP) at PT XYZ - Apriyanti, Yeni; Samanhudi, Didi; Safirin, M.T. (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
PT XYZ is a private company engaged in freight forwarding services in Surabaya - Waingapu. In its journey, the company experienced many challenges, which continuously improved its performance management, starting from financial issues, customers, internal business processes, and learning and growth. This study aims to determine the level of company performance and provide recommendations for improvements to the Key Performance Indicator below the target. The method used is the Balanced Scorecard (BSC) supported by the Analytical Hierarchy Process (AHP). The study results show that PT XYZ's company performance score in 2020 produced a score weight of 2.88 which is included in the good category. In contrast, in 2021, the company's performance made a weighted score of 2.78 which is included in the good category, and 2022, the company's performance had a weighted score of 2.26 which is included in the sufficient category. Internal Business Processes are the focus of improvement because the achievement score still needs to catch up to the target to improve PT XYZ's performance.